Traditions in world cinema - Badley, Linda; Palmer, R. Barton; Schneider, Steven Jay; Miller, Toby (New Brunswick, N.J. : Rutgers University Press, 2006)
Traditions in World Cinema brings together a colorful and wide ranging collection of world cinematic traditions—national, regional, and global—all of which are in need of introduction, investigation and, in some cases, critical reassessment. The movements described range from well-known traditions such as German expressionism, Italian neorealism, French, British, and Czech new wave, and new Hollywood cinema to those of emerging significance, such as Danish Dogma, postcommunist cinema, Brazilian post–Cinema Novo, new Argentine cinema, pre-independence African film traditions, Israeli persecution films, new Iranian cinema, Hindi film songs, Chinese wenyi pian melodrama, Japanese horror, and global found-footage cinema.

The essays, all written by recognized experts in the field, are jargon free and accessible to both general readers and students. In addition, each chapter is followed by a list of suggested films and readings, offering readers pathways to further viewing and study.

Bringing fresh insights to those movements that have provided significant and noteworthy alternatives to Hollywood, this book is an essential introduction to the rich diversity of world cinema.
Part I: European traditions ; Part II: Central, eastern and northern European traditions ; Part III: South American traditions ; Part IV: African and Middle Eastern traditions ; Part V: Asian traditions ; Part VI: American and transnational traditions
Bibliografija uz poglavlja. - Kazalo
Keywords: Motion pictures; filmska umjetnost